Analysing hosts’ and users’ perceptions towards coworking space: From the perspective of real estate agents - Choy, Christina Yee Lin (2022)
Over the past decades, the advancement of technology has shifted the way people work. With the increased flexibilization of workstyle, it is now possible to work anywhere and everywhere. However, employees still seek for a working environment that is able to stimulate collaboration and networking possibilities. This has led to the fast growth of coworking space as a new type of workspace concept. Coworking spaces offer a variety of spaces with ultimate flexibility. The aim of this study is to define the coworking hosts’ and users’ perceptions towards coworking spaces, specifically through the perspective of real estate agents in Malaysia. Data were collected by means of face-to-face interview with 13 respondents who were involved in the office leasing industry from different real estate companies in Kuala Lumpur, Malaysia. A thematic analysis was conducted in this study to analyse hosts’ and users’ perceptions towards coworking spaces. Results shows that the characteristics of coworking spaces can be categorized into three: physical, service, and leasing attributes. From the perspective of the agents, the characteristics of coworking space that drives users to coworking space are cost-effective, flexibility, services quality, networking and collaboration opportunities, and the working environment. Though a fair number of studies highlighted that CWS trend is high in demand nowadays, the agents observed there might be an oversupply issue in Malaysia. Nevertheless, they acknowledge and foresee the trend to stay even when the pandemic is over.